(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims at identifying the role of cash flow statement indicators in explaining stock prices of the banks listed in the Damascus Security Exchange. The research in theoretical part concept of cash flow statement, then it was determined the objective of cash flow statement and its importance, Finally the research introduced the indicators of cash flow statement and the most important financial ratios used to express them. To achieve the objectives of the research hypotheses and test the hypotheses, quarterly financial statement were collected during the period from the second quarter 2011 to the third quarter 2016. To analyze the research data, the fixed effects model is used- one of the Panel Data Method. The data have been analyzed by using Eviews 8. The researcher reached at the end of the search that the financial liquidity quality indicator, the profit quality indicator, and financial flexibility indicator, contributes to explain stock prices of banks listed in DSE. The researcher recommended that these banks have to work to provide quarterly indicators of cash flow statement on the site of DSE, because of the importance of these indicators in helping decision maker to evaluate the current situation of the bank. يهدف البحث للتعرف على دور مؤشرات قائمة التدفقات النقدية في تفسير أسعار أسهم المصارف المدرجة بسوق دمشق للأوراق المالية، وتناول البحث في جانبه النظري مفهوم قائمة التدفقات النقدية ثم تم تحديد أهداف القائمة وأهميتها، واخيراً تم التطرق إلى مؤشرات قائمة التدفقات النقدية وأهم النسب المالية المستخدمة للتعبير عنها. ولتحقيق أهداف واختبار فرضيات البحث تم جمع بيانات القوائم المالية الربعية للمصارف خلال الفترة الممتدة من الربع الثاني 2011 ولغاية الربع الثالث 2016. لغرض تحليل بيانات الدراسة تم استخدام أحد نماذج بانل وهو نموذج التأثيرات الثابتة. وقد تم تحليل بيانات الدراسة بالاعتماد على البرنامج الإحصائي Eviews 8. وتوصلت الباحثة في نهاية البحث إلى أن كلٍ من مؤشر جودة السيولة ومؤشر جودة الأرباح ومؤشر المرونة المالية يسهم في تفسير أسعار أسهم المصارف المدرجة بسوق دمشق للأوراق المالية، وأوصت الباحثة أن تعمل هذه المصارف على توفير مؤشرات قائمة التدفقات النقدية الربعية على موقع سوق دمشق للأوراق المالية، نظراً لأهمية هذه المؤشرات في مساعدة متخذ القرار من تقييم الوضع الحالي للمصرف.